Islam and Politics in the 20th Century Scholarship: A Journal Review of Indonesia - Mayasari, Nuki (DINIKA : Academic Journal of Islamic Studies, 2018)
Discourse on Islam and politics during the 20th century is inseparable with related scholarly publications about Indonesia, taking time on that period. Reviewing â€œIndonesiaâ€, a journal issued by Southeast Asia Program Publications at Cornell University, this writing mainly aims to report the notion of how Islam and politics were being represented in the international scholarly works. Three categorizations of sub-themes are gained by evaluating two numbers of â€œIndonesiaâ€, they are (1) group and hierarchy, (2) perception and knowledge dynamics, and (3) public figure. The categorizations are used as a framework in analyzing how the notion of Islam and politics was internationally perceived through scholarly works issued during that period. Â The result shows that the impression of the notion of Islam and politics tends to be perceived as a power for promoting groups formation. The power distribution is another critical substance which can be derived from the group formation. The role of religion, to this extent, can easily be used as a legitimate source for any critical political decision. Societal segregation can be considered as a result of a certain kind of discrepancies in the realm of power distribution among several groups of people. In other words, the role of Islam is very critical in shaping the political expression of the people in Indonesia.Â Â Keywords:Islam and politics, Group and Hierarchy, Public Figure